Extending the breeding range: Killdeer nesting in coastal northern South America. / Ampliando el rango reproductivo: anidación del playero gritón en la costa norte de Suramérica. - Contreras, Francisco J.; Salas, Vanessa G.; Fernández-Ordóñez, Juan C.; Naveda-Rodríguez, Adrián (Anartia, 2020)
ABSTRACT We provide the first evidence of Killdeer (Charadrius vociferus) as a resident species in coastal Northern South America. Our observations correspond to 17 sightings and one breeding record of Killdeer in the non-breeding range of northwestern Venezuela during the breeding seasons of 2019 and 2020. RESUMEN Se muestra la primera evidencia del playero gritón (Charadrius vociferus) como una especie residente en la costa norte de Suramérica. Nuestras observaciones se basan en 17 avistamientos y un registro reproductivo en el noreste de Venezuela durante la temporada de anidación 2019 y 2020, el cual se encuentra fuera del área de anidación conocida previamente para la especie.